Raising hell, living well : freedom from influence in a world where everyone wants something from you - Elefante, Jessica (Ballantine Books, 2023)
"An unabashed guide and rueful confessional that lays bare the troublesome impact of influence in our culture and offers the freedom of living intentionally without it. Jessica Elefante Davis is a master manipulator. Or, she used to be. Her hope was to live outside the confines of traditional expectations. Rather than falling prey to the everyday influences pulling the strings, she attempted to become free from them by pulling the strings herself. Throughout her journey from bad influence to award-winning corporate strategist she collected nuggets of knowledge that all seemed to come down to one thing: influence-using it and abusing it. She soon began to wonder: was she the one avoiding it-or was she wielding it? Elefante Davis, now a reformed brand strategist, leads us through her own misadventures to open the door to a freer way of living. She shines a light on the forces attempting to persuade our every choice: what we buy, how we behave, and which values we embrace. In a noisy world overwhelmed by in-your-face everything, understanding-first How-Come, then How-To-is the key to hearing our own voice. With her groundbreaking take on intentional living, you'll learn a simple practice to uncomplicate how the powers-that-be attempt to modify our behaviors: Spot the Folklore: the myths preached so widely that we accept these influences as fact End the cycle of Folktales: the stories we tell ourselves to try to fit within the accepted standards Embrace the Folk Rebellion: a moment to pause and assess the influences so we can make choices that are true to ourselves After a life-saving, game-changing kick in the guts, Elefante Davis came to terms with the boxes she got stuck in and, regrettably, created for others. Unpretentious, ingenious, and devil-hearted, Raising Hell, Living Well holds out a hand to help you climb out from under the influence too"--